2010
DOI: 10.1037/2152-0828.1.s.13
|View full text |Cite
|
Sign up to set email alerts
|

Online “predators” and their victims: Myths, realities, and implications for prevention and treatment.

Abstract: The publicity about online "predators" who prey on naive children using trickery and violence is largely inaccurate. Internet sex crimes involving adults and juveniles more often fit a model of statutory rape-adult offenders who meet, develop relationships with, and openly seduce underage teenagers-than a model of forcible sexual assault or pedophilic child molesting. This is a serious problem, but one that requires approaches different from those in current prevention messages emphasizing parental control and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
200
1
20

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(239 citation statements)
references
References 82 publications
12
200
1
20
Order By: Relevance
“…These sites can provide important access to role models and support systems that adolescents may not have in their offline social circles. Although the majority of online interactions are benign, 29 contact with a person whose identity has not been confirmed can be a dangerous situation for adolescent girls. Many adolescents do not possess the necessary skills to ward off sexual advances whether online or in person.…”
Section: Discussionmentioning
confidence: 99%
“…These sites can provide important access to role models and support systems that adolescents may not have in their offline social circles. Although the majority of online interactions are benign, 29 contact with a person whose identity has not been confirmed can be a dangerous situation for adolescent girls. Many adolescents do not possess the necessary skills to ward off sexual advances whether online or in person.…”
Section: Discussionmentioning
confidence: 99%
“…It is useful to recall the development of CP laws in the US and in the world (SeigfriedSpellar et al, 2012). After that, we present threats for children by briefly looking at profiles of online predators (Wolak et al, 2010;Seigfried-Spellar, 2013), cyberbullying (Huitsing et al, 2012), detecting children (Murphy, 2012), and risk of online games (Penna et al, 2010).…”
Section: Children-oriented Attacksmentioning
confidence: 99%
“…While identifying criminals for OSN-initiated crimes, it should be noted that these criminals do not necessarily use fake identities such as representing themselves as children. Wolak et al (2010) analyzed internet-initiated sex crimes and found out that the victims who were teenagers aged 13 to 17 knew that they were communicating with an adult, could lead to a physical meeting and engage in a sexual activity. Hence, internet-initiated sex crimes are not necessarily a result of online deceptive information.…”
Section: Threats For Childrenmentioning
confidence: 99%
“…Individuals share identity-related (e.g., location, date of birth) or activityrelated information, as well as details of emotions and relationships on social media. These details can be used by offenders to identify indicators of vulnerability and to make initial contact with potential victims 49 for the purposes of grooming, dating scams and other fraudulent activities. It can also be used for the purposes of harassment and stalking by individuals, or to guess passwords or utilise social engineering techniques, as well as hacking bank and social media accounts.…”
Section: Online Behaviours Exposing Individuals To Risk Of Victimisationmentioning
confidence: 99%